2010
DOI: 10.1158/1078-0432.ccr-10-0523
|View full text |Cite
|
Sign up to set email alerts
|

Histone γH2AX and Poly(ADP-Ribose) as Clinical Pharmacodynamic Biomarkers

Abstract: Tumor cells are often deficient in DNA damage response (DDR) pathways, and anticancer therapies are commonly based on genotoxic treatments using radiation and/or drugs that damage DNA directly or interfere with DNA metabolism, leading to the formation of DNA double-strand breaks (DSB), and ultimately to cell death. Because DSBs induce the phosphorylation of histone H2AX (γH2AX) in the chromatin flanking the break site, an antibody directed against γH2AX can be employed to measure DNA damage levels before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(202 citation statements)
references
References 108 publications
7
193
0
2
Order By: Relevance
“…Nonetheless, it can be concluded that DMN induced changes in histone proteins by way of reducing their extents of poly ADPribosylation during the initiation stage of DMN induced carcinogenesis. The PAR of histone proteins observed in our study confirms the earlier report of histones being the major target of cellular PAR (Kma and Sharan, 2006;Fontan-Lozano et al, 2010;Redon et al, 2010), making histones the most preferred target proteins for PAR.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, it can be concluded that DMN induced changes in histone proteins by way of reducing their extents of poly ADPribosylation during the initiation stage of DMN induced carcinogenesis. The PAR of histone proteins observed in our study confirms the earlier report of histones being the major target of cellular PAR (Kma and Sharan, 2006;Fontan-Lozano et al, 2010;Redon et al, 2010), making histones the most preferred target proteins for PAR.…”
Section: Discussionsupporting
confidence: 92%
“…Detection of Irradiation-induced Phosphorylation in Irradiated Bulb Hair-Phosphorylated H2AX has been identified as a potentially useful biomarker of exposure to DNA-damaging agents (52). We thought that Hsp90␣, which is highly abundant in all cell types, would be a useful alternative marker.…”
Section: Activation Of Dna-pk By Small Dna Molecules Leads To Hsp90␣ mentioning
confidence: 99%
“…Correlation between Basal P-Hsp90␣ Levels and ␥-H2AX Content in Human Tumors and Possible Use of P-Hsp90␣ as a Biomarker of DNA Damage-Phosphorylated H2AX has been identified as a useful biomarker in clinical oncology (52,53). First, ␥-H2AX quantification can be used to assess the efficacy of DNA damage-inducing chemo-or radiotherapy (25).…”
Section: Activation Of Dna-pk By Small Dna Molecules Leads To Hsp90␣ mentioning
confidence: 99%
“…Although some drugs were specifically developed for targeted cancer chemotherapy (1,2), most anti-cancer drugs used today are DNA-damaging agents that induce cancer cell death by interfering with checkpoint responses (3)(4)(5)(6)(7)(8)(9). Because these anti-cancer drugs are administered without a specialized delivery system, they often cause side effects.…”
mentioning
confidence: 99%